Effects of Intravenous Glucose on Blood Potassium in Cattle - Mudroň Pavol; Helin Emma (Folia Veterinaria, 2023)
The aim of this study was to confirm whether a rapid intravenous glucose administration can lead to a significant drop in blood potassium levels in cattle. For this study, seven cattle were used according to internationally recognized guidelines for animal welfare. Glucose at a dose of 1 g.kg−1 body weight was administrated intravenously and then blood samples were taken before and 0.5, 1, 2, 4, and 6 hours after administration of glucose for measurement of potassium and glucose blood concentrations. For statistical analysis of glucose effects on both glucose and potassium levels one-way analysis of variance (ANOVA) for repeated measures was used. ANOVA showed a strong significant effect of the glucose administration on plasma glucose levels (P < 0.001). The glucose administration resulted in a mean plasma increase from 4.2 mmol.l−1 to 21.2 mmol.l−1 within the first minutes after the administration followed by a steady decrease back to the initial values. In contrast, ANOVA showed no significant effect of the glucose administration on plasma potassium levels. In conclusion, the glucose does not have a potassium-lowering effect when administered in a single large intravenous dose.